Pemahaman Generasi Muda terhadap Representasi Keteladanan Hidup pada Ilustrasi Wayang - Natalia Hasti Lumenta (Departement of Mathematics Education, 2023)
Indonesian people pride towards wayang is increasing since being acknowledged by UNESCO as a Masterpiece of the Oral and Intangible Heritage of Humanity. Nevertheless, the influence of global culture has caused crisis on national cultural identity and changed the behavior and mindset of young people. Massive efforts are needed in perseveres this noble culture to the next generation. Therefore, wayang revitalization is carried out to maintain its existence, such as representing wayang characters with modifications to modern forms presented in illustrative products. Peirce’s semiotic sign applied on the illustration in the form of icons, indexes and symbols as a form of visual communication that represents the exemplary values of wayang in everyday life. This research was conducted to find out whether young audiences can identify a number of modified wayang characters and understand their exemplary illustrations. This research employs research and development (R&D) method. Image testing and interviews were conducted with a number of respondents from young people with an interest in visual communication design (DKV) or illustration. The result shows young audiences are able to identify wayang characters and understand their role models through the semiotic signs displayed, even though they do not yet have knowledge about wayang.